2013
DOI: 10.1007/s10695-013-9868-5
|View full text |Cite
|
Sign up to set email alerts
|

n-3 LC-PUFA deposition efficiency and appetite-regulating hormones are modulated by the dietary lipid source during rainbow trout grow-out and finishing periods

Abstract: Largely attributable to concerns surrounding sustainability, the utilisation of omega-3 long-chain polyunsaturated fatty acid-rich (n-3 LC-PUFA) fish oils in aquafeeds for farmed fish species is an increasingly concerning issue. Therefore, strategies to maximise the deposition efficiency of these key health beneficial fatty acids are being investigated. The present study examined the effects of four vegetable-based dietary lipid sources (linseed, olive, palm and sunflower oil) on the deposition efficiency of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
33
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 38 publications
6
33
2
Order By: Relevance
“…A similar observation is true for some fatty acid classes, particularly saturated fatty acids and monounsaturated fatty acids, which also appear to enhance the retention of ω3 LC PUFA in the fillets of some fish species. These observations have been found in Atlantic cod (Gadus morhua) [31], sunshine bass (Morone chrysops x Morone saxatilis) [36], Murray cod (Maccullochella peelii peelii) [37] and rainbow trout [35]. This approach has been given the more specific definition of the 'ω3 LC PUFA sparing effect' as found in Atlantic salmon [36].…”
Section: Terrestrial Plant Oils In Aquaculture Feedsmentioning
confidence: 92%
See 2 more Smart Citations
“…A similar observation is true for some fatty acid classes, particularly saturated fatty acids and monounsaturated fatty acids, which also appear to enhance the retention of ω3 LC PUFA in the fillets of some fish species. These observations have been found in Atlantic cod (Gadus morhua) [31], sunshine bass (Morone chrysops x Morone saxatilis) [36], Murray cod (Maccullochella peelii peelii) [37] and rainbow trout [35]. This approach has been given the more specific definition of the 'ω3 LC PUFA sparing effect' as found in Atlantic salmon [36].…”
Section: Terrestrial Plant Oils In Aquaculture Feedsmentioning
confidence: 92%
“…As a result, the immediate thought is that plant oils best suited as a substitute for FO should contain high levels of ω3 PUFA (LNA) and lower amounts of LA, in order to increase the ω3/ω6 ratio. However, a study by Francis et al [35] contradicts this idea because it was found that ω6 PUFA (sunflower oil diet) appeared to 'spare' the catabolism of ω3 LC PUFA and, as such, resulted in the highest retention of these fatty acids by rainbow trout. These results suggest new nutritional approaches to maximise the maintenance of the qualitative benefits of fish oils when they are used in feeds for aquaculture species [35].…”
Section: Terrestrial Plant Oils In Aquaculture Feedsmentioning
confidence: 99%
See 1 more Smart Citation
“…Soybean and canola, which are the most commonly used ones, have poor amounts of n-3 highly unsaturated fatty acid (HUFA), but soybean oil is rich source of polyunsaturated fatty acid (PUFA), mainly linoleic (LA; 18:2 n-6) and canola oil is rich about monounsaturated fatty acid (MUFA) mainly oleic acid (OA; 18:1n-9) (Fountoulaki et al, 2009). For this reason they are considered as alternate oil sources for fresh water and marine fish species (Caballero et al, 2002;Izquierdo et al, 2005;Montero et al, 2005;Piedecausa et al, 2007;Fountoulaki et al, 2009;Turchini et al, 2009;Arslan et al, 2012;Francis et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The results of these studies were acceptable in terms of growth performance, in addition to this, their experimental diets contained sufficient amount of fish meal from 381 g to 500 g per kg. On the other hand, some promising results also were yielded from the studies in which total replacement of fish oil with vegetable oil were carried out using fishmeal-based diets (fish meal content from 383 g to 600 g per kg)in different fish species (Mourente et al, 2005;Piedecausa et al, 2007;Turchini et al, 2011;Altundağ et al, 2014;Francis et al, 2014;Yılmaz and Eroldoğan, 2015).…”
Section: Introductionmentioning
confidence: 99%